Therapeutic effect of exogenous tumor necrosis factor-stimulating protein 6 intervention on lung injury in newborn rats by intrauterine infection - Qing-yan Kang; Zhi-yong Sun; Xi-zhe Yuan; Zi-yang Su; Dong-yuan Xu; Wei Zhu (Scientific Reports)
Abstract To investigate the therapeutic effect of exogenous tumor necrosis factor-stimulating protein 6(TSG-6) on lung injury in newborn rats induced by intrauterine infection, and to analyze its underlying mechanism. Twelve pregnant rats were randomly divided into a blank control group, a negative control group, a model group, and a TSG-6 treatment group. The blank control group was not modeled. The negative control group was injected with normal saline (NS) intraperitoneally on gestation day (E)14, and the remaining two groups were intraperitoneally injected with lipopolysaccharide at 0.6 mg/kg × body weight(kg) on E14 to establish the intrauterine infection model. The negative control and model groups were injected with NS via the tail vein on E16, and the TSG-6 treatment group was injected with TSG-6 at 0.25 mg/kg × body weight(kg) via the tail vein on E16. After delivery, the placentas of pregnant rats and the right lungs of newborn rats on postnatal day (P) 3, 7, and 14 were stained with hematoxylin-eosin to observe the inflammatory infiltration of placentas, the pathology of the lungs, and the radical alveolar count (RAC) was performed. The left lung tissues of newborn rats were collected on P3, P7d, and P14. Using Enzyme-linked immunosorbent assay (ELISA) kits to measure the levels of TSG-6, tumor necrosis factor-α(TNF-α), vascular endothelial growth factor (VEGF), and Interleukin-6 (IL-6) in lung tissues of newborn rats. Compared with the model group, the growth of the control group and the TSG-6 treatment group was better, the bronchial epithelial structure of the control and TSG-6 treatment group was intact, and the epithelial cells were normal and closely arranged. The levels of RAC, VEGF, and TSG-6 in the TSG-6 treatment group were significantly increased, and the levels of IL-6 and TNF-α were significantly decreased at the early stage of life compared with the model group; the differences were statistically significant (P < 0.05). TSG-6 intervention can reduce the inflammatory response of pregnant rats with intrauterine infection and significantly improve the pathological degree of lung injury in newborn rats caused by intrauterine infection. Its mechanism may be related to promoting the increase of TSG-6 and VEGF levels, regulating the balance of inflammatory factors and promoting tissue repair.